Developing a TPACK-Based Module to Improve Pre-Service Social Studies Teachers’ Knowledge, Attitude, Skills and Values - Ahmad Nurhuda; Zainimal Zainimal; Nisa Ulaini; Aulia Rahmi Putri; Tuti Alawiyah (Tarikhuna: Journal of History and History Education, 2024)
This research aims to develop a learning module based on Technological Pedagogical Content Knowledge (TPACK) to increase knowledge, attitude, skill and values of the students of Social Studies Education at State Islamic University (UINs) in Sumatera. Using research and development (RD) methodology, this study involved 40 students from UIN Imam Bonjol Padang and UIN Sultan Syarif Kasim Riau. The result of this research shows that students were still facing challenges in intergrating technology in learning process. Despite using digital tool like PowerPoint, the intergration within the pedagogical context was suboptimal. The students desire to obtain an interactive and relevant learning experiences. The developed module integrates Content Knowledge, Pedagogical Knowledge, and Technological Knowledge, using media such as Padlet and Wordwall. Expert validation indicated that the module is highly suitable for use, with an average score of 84%. It is anticipated that this module will improve the quality of Social Studies learning, equip students with relevant skills, and integrate Islamic values. With this approach, the module is expected to enhance student understanding and engagement, as well as adaptability to future curriculum developments.